Amending Ethics Committee Sanction Recommendations in the House of Representatives. (2nd January 2023) - Straus, Jacob R.
Abstract: The Constitution provides Congress with the power to punish and discipline its Members. Since the 90th Congress (1967–1968), the House Ethics Committee has been authorized to investigate allegations of misconduct and recommend punishments. This paper examines seven instances where the House Ethics Committee has recommended punishment and the House has considered an amendment to increase or decrease the proposed sanction. Using a combination of case studies and a roll call vote data, this paper finds that demographic similarities between the accused and the voting Member (race, party, and state delegation), partisanship, and serving on the Ethics Committee influence whether a Member might choose to support an alternative sanction. For amendments that propose an increased penalty, same state delegation (negative effect), co-partisanship (positive effect), race (positive effect), ideology (positive effect), and type of scandal (negative effect) matter. For decreased penalties, same state delegation (positive effect), race (positive effect), and ideology (negative effect) matter. For all amendments, being an Ethics Committee member is a strongly negative predictor. These findings imply that committee members attempt to protect the committee's recommendation, that demographic similarities matter when Members are making sanction decisions, and that ideology is a driving factor in deciding to support a change in ethics penalty.